1997
DOI: 10.1063/1.118273
|View full text |Cite
|
Sign up to set email alerts
|

Hole-filling of persistent spectral holes in the excitonic absorption band of CuBr quantum dots

Abstract: Persistent spectral-holes ͑p-SH͒ are burned in the Z 1,2 excitonic band of CuBr nanocrystals by a pulsed laser excitation. The annealing of p-SH is studied by three types of hole-filling ͑HF͒ experiments: ͑i͒ the spontaneous HF, ͑ii͒ thermally-induced HF, and ͑iii͒ the laser-induced HF. Results are compared to the well developed theory of the persistent spectral hole-burning ͑p-SHB͒ in the system of molecules in amorphous matrices. Both p-SHB and HF phenomena can be explained within the framework of a photoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Furthermore, cuprous chloride (CuCl) has been used as a source material for Cu and Cl ions to enhance the catalytic activities of the oxide based catalysts such as Cu 2 O, NaTaO 3 , and K 2 La 2 Ti 3 O 10 . , However, the catalytic activities of pure CuCl based catalysts toward HER and OER are yet to be investigated. The copper halide based materials (CuCl, CuBr, and CuI) are an interesting class of materials , because of their direct band gap (3.39 eV for CuCl, 2.91 eV for CuBr, and 2.95 eV for CuI) and optoelectronic applications. , Interestingly, the band structure of these materials shows similar dispersion though the valence band edge position changes with the nature of the halide. , However, the conduction band edge position remains more or less the same irrespective of the nature of the halide with respect to the absolute vacuum scale (AVS). , Interestingly, among all these Cu based halides and some of the copper oxide based materials (such as Cu 2 O and CuO), CuCl has a more stabilized valence band, which is certainly promising for the water oxidation reaction. Therefore, it would be more enthusiastic to investigate whether CuCl nanostructure based catalysts can be promising for the overall water splitting reaction as CuCl has already been synthesized in different nanostructural forms (nanoplatelets, quantum cubes, and quantum dots). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cuprous chloride (CuCl) has been used as a source material for Cu and Cl ions to enhance the catalytic activities of the oxide based catalysts such as Cu 2 O, NaTaO 3 , and K 2 La 2 Ti 3 O 10 . , However, the catalytic activities of pure CuCl based catalysts toward HER and OER are yet to be investigated. The copper halide based materials (CuCl, CuBr, and CuI) are an interesting class of materials , because of their direct band gap (3.39 eV for CuCl, 2.91 eV for CuBr, and 2.95 eV for CuI) and optoelectronic applications. , Interestingly, the band structure of these materials shows similar dispersion though the valence band edge position changes with the nature of the halide. , However, the conduction band edge position remains more or less the same irrespective of the nature of the halide with respect to the absolute vacuum scale (AVS). , Interestingly, among all these Cu based halides and some of the copper oxide based materials (such as Cu 2 O and CuO), CuCl has a more stabilized valence band, which is certainly promising for the water oxidation reaction. Therefore, it would be more enthusiastic to investigate whether CuCl nanostructure based catalysts can be promising for the overall water splitting reaction as CuCl has already been synthesized in different nanostructural forms (nanoplatelets, quantum cubes, and quantum dots). …”
Section: Introductionmentioning
confidence: 99%
“…CuBr is a I–VII compound semiconductor material with great potential for short-wavelength applications due to its extremely large excitonic binding energy (∼108 meV) and direct band gap (∼3.1 eV at 300 K). It exhibits good transparency (>80%) throughout the major portion of the visible region (above 420 nm) and shows strong absorption in the UV-violet region of the spectrum . Although, there are numerous reports on the excitonic and nonlinear optical properties of CuBr, there are relatively few studies on the semiconducting properties of this material. The poor hole conductivity of as-deposited (ASD) CuBr films represents a major limitation for the adoption of these materials, and thus the deposition of good quality CuBr films with increased p-type conductivity would be an extremely important development for future applications of this material system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, I-VII γ -cuprous halides semiconductors 20 such as CuCl, CuBr, and CuI have drawn attention 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 because these are zincblende direct band-gap semiconductors (3.3 eV for CuCl, 2.91 eV for CuBr and 2.95 eV for CuI) and have large exciton binding energies (190 meV for CuCl, 108 meV for CuBr and 58 meV for CuI) with their lattice constants closely matched to that of Si as can be seen by the table 1 . From this table, one can see that the lattice constant of Si, 0.543 nm, is very closely matched to that of CuCl, 0.542 nm.…”
mentioning
confidence: 99%
“…Researches on the cuprous halides semiconductors have been focused on the following areas over the past decade: (1) spectroscopic and theoretical studies of band structures 26 27 28 29 30 31 32 33 , (2) photoluminescence studies of I-VII quantum dots embedded in NaCl crystals and glasses 22 24 25 33 , (3) surface studies of the growth mechanisms involved in the hetero epitaxy, and single crystal and poly crystal layer growth on Si and GaAs 23 35 36 37 38 39 40 . Especially, Nishida et al 23 demonstrated single crystal thin layera growth on GaAs and Si using ultra high vacuum (UHV) molecular beam epitaxy (MBE).…”
mentioning
confidence: 99%